2021
DOI: 10.18240/ijo.2021.03.10
|View full text |Cite
|
Sign up to set email alerts
|

High interpretable machine learning classifier for early glaucoma diagnosis

Abstract: AIM: To develop a classifier for differentiating between healthy and early stage glaucoma eyes based on peripapillary retinal nerve fiber layer (RNFL) thicknesses measured with optical coherence tomography (OCT), using machine learning algorithms with a high interpretability. METHODS: Ninety patients with early glaucoma and 85 healthy eyes were included. Early glaucoma eyes showed a visual field (VF) defect with mean deviation >-6.00 dB and characteristic glaucomatous morphology. RNFL thickness in every qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Prior studies have also shown strong discriminative ability between healthy and glaucomatous eyes with these methods. 22 , 41 …”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have also shown strong discriminative ability between healthy and glaucomatous eyes with these methods. 22 , 41 …”
Section: Discussionmentioning
confidence: 99%
“…In this review of related work, we will mainly focus on interpretability techniques applied to CNNs for glaucoma diagnosis, with special emphasis on the use of surrogate models. The use of tabular clinical data to fit interpretable machine learning models has been widely explored in glaucoma diagnosis, either alone [20,21] or in combination with fundus images [22][23][24]. Another common approach is the extraction of relevant features from images.…”
Section: Related Workmentioning
confidence: 99%
“…For example, Wroblewski et al ( 2009 ) used support vector machines (SVMs) to provide a valid clinical diagnosis of glaucoma based solely on visual field data. Escamez et al ( 2021 ) developed a classifier for predicting glaucoma eyes based on peripapillary retinal nerve fiber layer (RNFL) thicknesses measured with OCT. The other is a multimodal fusion image, which is a combination of two or more types of data.…”
Section: Introductionsmentioning
confidence: 99%